2016
DOI: 10.5152/balkanmedj.2016.16220
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Dual-source CT and the Upshot it creates on Both Heart Rate and Image Quality

Abstract: Background: Early detection of coronary artery disease (CAD) is important because of the high morbidity and mortality rates. As invasive coronary angiography (ICA) is an invasive procedure, an alternative diagnostic method; coronary computed tomography angiography (CTA), has become more widely used by the improvements in detector technology. Aims: In this study, we aimed to examine the accuracy and image quality of high-pitch 128-slice dual-source CTA taking the ICA as reference technique. We also aimed to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…In most cases of this study (80 of 84 patients, 95.2%), the entire heart could be scanned within a 140 mm. The mean ED of 1.9 mSv in this study is higher than that reported in some recent studies with mean ED less than 1.0mSv [28][29][30]. However, different modes of high-pitch with dual-source CT were used in those studies, also with inclusion of patients with different heart rates.…”
Section: Discussioncontrasting
confidence: 64%
“…In most cases of this study (80 of 84 patients, 95.2%), the entire heart could be scanned within a 140 mm. The mean ED of 1.9 mSv in this study is higher than that reported in some recent studies with mean ED less than 1.0mSv [28][29][30]. However, different modes of high-pitch with dual-source CT were used in those studies, also with inclusion of patients with different heart rates.…”
Section: Discussioncontrasting
confidence: 64%
“…Insufficient data were provided by one study, and it was therefore excluded from the analysis. 19 Of the remaining studies, six contained patient‐level accuracy information and were included, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…4,[14][15][16] Four studies that reported patient-level diagnostic accuracy data were included in the review. [17][18][19][20] Whilst the primary aim of these studies was not to directly study high HRs, they provided subgroup data directly pertinent to the review question.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…63,70,83 Scanners with faster rotation times (better temporal resolution) or an increased number of x-ray sources permit higher heart rate cutoffs for prospectively ECG-triggered acquisition mode, which is associated with substantially lower radiation dose as compared with retrospectively ECG-gated acquisition mode. 63,70,83 Addition of "adaptive" or arrhythmia rejection feature in prospectively ECG-triggered acquisition mode enables the scanners to reject scanning in beats with irregular rhythm so that obtain diagnostic quality exams at reduced radiation dose even in patients with variable heart rates, such as atrial fibrillation. Without the arrhythmia rejection algorithms for prospectively ECG-triggered mode, patients with variable heart rates would require much higher radiation doses from retrospectively ECG-gated acquisition mode with conservative ECG-based tube current modulation.…”
Section: Miscellaneous Dose-reduction Strategiesmentioning
confidence: 99%
“…66,67 High-pitch helical (HPH) acquisition mode with fast table speed and prospective ECG triggering enables coverage of the entire heart within one cardiac cycle. Several studies on HPH mode for CCTA in pediatric and adult populations 16,63,[68][69][70] have reported good diagnostic quality and consistently low mean radiation dose (0.8 to 1.3 mSv) ( Table 2). The HPH is particularly advantageous in children or young adults for assessment of coronary artery anomalies and anatomic assessment in patients with congenital heart disease (when information regarding cardiac function is not needed).…”
Section: High-pitch Helical Acquisitionsmentioning
confidence: 99%